ACPA Alleviates Bleomycin-Induced Pulmonary Fibrosis by Inhibiting TGF-β-Smad2/3 Signaling-Mediated Lung Fibroblast Activation - Chen, Dongxin; Tang, Huirong; Jiang, Hongchao; Sun, Lei; Zhao, Wenjuan; Qian, Feng (Frontiers in Pharmacology, 2022)
Idiopathic pulmonary fibrosis (IPF) is a life-threatening disease with limited therapeutic options. The involvement of cannabinoid type 1 receptors (CB1R) have been indicated in fibrotic diseases but whether or not the activation of CB1R can be benefit for fibrosis treatment is controversial. In this study, we investigated the effects of arachidonoylcyclopropylamide (ACPA), as a selective CB1R agonist, on bleomycin (BLM)-induced pulmonary fibrosis. We showed that ACPA treatment significantly improved the survival rate of BLM-treated mice, alleviated BLM-induced pulmonary fibrosis and inhibited the expressions of extracellular matrix (ECM) markers such as collagen, fibronectin and α-SMA. The enhanced expressions of ECM markers in transforming growth factor-beta (TGF-β) challenged primary lung fibroblasts isolated from the lung tissue of mice were inhibited by ACPA treatment in a dose-dependent manner, as well as the fibroblast migration triggered by TGF-β was dose-dependently diminished after ACPA administration. Moreover, the increased mRNA level of CB1R was observed in both lung fibroblasts of BLM-induced fibrotic mice in vivo and TGF-β challenged primary lung fibroblasts in vitro. CB1R-specific agonist ACPA significantly diminished the activation of TGF-β–Smad2/3 signaling, i.e., the levels of p-Smad2 and p-Smad3, and decreased the expressions of downstream effector proteins including slug and snail, which regulate ECM production, in TGF-β challenged primary lung fibroblasts. Collectively, these findings demonstrated that CB1R- specific agonist ACPA exhibited antifibrotic efficacy in both in vitro and in vivo models of pulmonary fibrosis, revealing a novel anti-fibrosis approach to fibroblast-selective inhibition of TGF-β-Smad2/3 signaling by targeting CB1R.